Resolva a equação 4.(x – 2) – 5.(2 – 3x) = 4.(2x – 6)
(A)- 6/11
(B)-3/10
(C)-5/7
(D)4/3
(E)6/13
Soluções para a tarefa
Respondido por
6
Resposta ↓
Letra A é a correta = - 6/11
Explicação passo-a-passo:
4.(x - 2) - 5.(2 - 3x) = 4.(2x - 6)
4x - 8 - 10 + 15x = 8x - 24
4x + 15x - 8x = - 24 + 10 + 8
11x = - 6
x = - 6 / 11
A = correta
Perguntas interessantes
Português,
6 meses atrás
Matemática,
6 meses atrás
História,
6 meses atrás
Matemática,
8 meses atrás
Matemática,
8 meses atrás
Português,
1 ano atrás
Biologia,
1 ano atrás